Experimental studies on reactive distillation of propionic acid using n-butanol as entrained - Kalakuntala, Raju.; Navya, R; Sisira, T; V. Basava Rao, V; Surnani, Srinath. (International Journal of Engineering and Technology, 2018)
Reactive distillation is a cost effective chemical engineering process intensification method which involves the reaction and separation simultaneously in a single unit. In the present work the system selected was Propionic acid and n-butanol which undergoes esterification reaction to form butyl propionate. Propionic acid is an important raw material from a biodegradable polymer. The experiments were done in both conventional batch distillation and reactive distillation. In conventional batch distillation no catalyst were used were as in reactive distillation amberlite catalyst used with various weight percentage. several experiments performed by varying the initial concentration(i.e. 0.1,0.2,0.4,0.6,0.8,0.99) of Propionic acid, mole ratios of Propionic acid & n-butanol(that is 1:1 ,1:1.5 ,1:2 And amberlite catalyst weight percent (i.e. 1,2 and 3).the conventional batch distillation and reactive distillation were compared. it is found that maximum conversion obtained in conventional distillation process is 81% and in reactive distillation is 95.1% at the optimum conditions are at initial concentration 0.6 ,mole ratio 1:2 And amberlite catalyst weight percentage 3 .And the recovery of water is more in reactive distillation as compared with the conventional batch distillation .So reactive distillation process is better than conventional distillation.Â Â